"({y^2} - 2xy)dx - (2xy - {x^2})dy = 0"
"- \\frac{{dy}}{{dx}}( - {x^2} + 2xy) + {y^2} - 2xy = 0"
Let "y(x) = xv(x)", which gives "\\frac{{dy}}{{dx}} = x\\frac{{dv}}{{dx}} + v" :
"- ( - {x^2} + 2{x^2}v)\\left( {x\\frac{{dv}}{{dx}} + v} \\right) + {x^2}{v^2} - 2{x^2}v = 0"
Simplify:
"- {x^2}\\left( { - x\\frac{{dv}}{{dx}} + {v^2} + v + 2x\\frac{{dv}}{{dx}}v} \\right) = 0"
Solve for "{\\frac{{dv}}{{dx}}}":
"\\frac{{dv}}{{dx}} = \\frac{{ - {v^2} - v}}{{x(2v - 1)}}"
Divide both sides by "\\frac{{ - {v^2} - v}}{{2v - 1}}:"
"\\frac{{\\frac{{dv}}{{dx}}(2v - 1)}}{{ - {v^2} - v}} = \\frac{1}{x}"
Integrate both sides with respect to x:
"\\int {\\frac{{\\frac{{dv}}{{dx}}(2v - 1)}}{{ - {v^2} - v}}} dx = \\int {\\frac{1}{x}} dx"
Evaluate the integrals:
"- 3\\ln (v + 1) + \\ln v = \\ln x + C"
Substitute back:
"- 3\\ln (\\frac{y}{x} + 1) + \\ln \\frac{y}{x} = \\ln x + C"
Comments
Leave a comment